Hydrocortisone acetate-injected piglets have a larger pancreas and greater mucosal weight and lactase, maltase, and sucrose activities in the duodenum - K K Kreikemeier; D L Harmon; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1989)
One litter of 12 piglets was used in a completely random design to evaluate the effects of hydrocortisone acetate injections on organ weight and carbohydrase activities. Dams' milk was the only food source available to the piglets. When they were 7 d old, six pigs were injected with hydrocortisone acetate (50 mg/kg BW; 50 mg/ml) and six others were injected with an equal volume of saline (1 ml/kg BW). When the pigs were 14 d old, tissues were collected, weighed, and analyzed for carbohydrase activities. Hydrocortisone acetate injection had no effect on pig daily gain (d 7 to 14), liver weight, spleen weight, or small intestinal (SI) length. However, it did increase pancreatic weight by 29%. Consequently, total pancreatic alpha-amylase was 38% greater in hydrocortisone-injected pigs. Hydrocortisone also increased duodenal mucosal weight (per cm of SI) by 23%, duodenal lactase activity (per cm of SI) by 44%, duodenal maltase activity (per cm of SI) by 163% and duodenal sucrase activity (per cm of SI) by 214%. There was little effect on disaccharidase activities in the jejunum or ileum. We conclude that hydrocortisone acetate may be useful to stimulate pancreatic growth and duodenal mucosal weight as well as lactase, maltase, and sucrase activity in 7-d-old pigs.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Piglet; Glucocorticoid; Pancreas; Small intestine; Intestinal mucosa; Carbohydrases